Biomechanics in Sprint Running - Shim, J.
Reviewing and comparing biomechanical variables affecting sprint performance studied by many researchers, you can not only come up with the factors to improve the performance and utilize them to train sprinters, but also apply them to many forms of human locomotions and also sports. There are so many factors affecting the sprinters¡¯ performance. The factors can be divided into kinematic factors and kinetic factors in which the one is related with the description of motion and the other is concerned with the action of force. The kinematic factors in sprint can be exemplified with distance between two blocks, block obliquity, block time, angles and alignments of body parts, stride length and rate, ground contact and flight time and position, velocity, and acceleration of total body COM. The kinetic factors can be force, impulse, power and so on. It could be easily thought that the shorter the reaction time is, the higher the performance level is because the short reaction time could reduce the total elapsed time during a sprint even though many results of research have proved it is not proportional to sprinters¡¯ performances. As far as the 3 types of block spacing are concerned, the types are defined with the unit of meter with no respect of the height of sprinters and the length of sprinters¡¯ body segments. So the medium start for some sprinters could be the elongated start or the bunch start. The better way to define three of them is to use the percent length from fingers on a start line to a front foot and from the front foot to a rear foot. During the block phase and post-block phase, it is important to produce as much force as possible to shorten the elapsed time. The more skilled sprinters may be better able to utilize elasticity of the lower extremity extensor muscles than the less skilled counterparts in order to produce larger amount of force. That is the one of the main reason the skilled have more ground reaction force than the others. The important issues in the phases after start are braking force and propulsive force. Sprinters need to reduce the braking force and increase the propulsive force. Sprinters can dramatically reduce the braking force which changes the vertical displacement of total body COM as small as possible. Braking and propulsion phases affect the velocity and reduction of the braking force especially causes to increase acceleration. In most studies reviewed, the number of subjects was small, in which it is sometimes difficult to generalize the results and apply them to other sprint runners. The difficulty to apply them easily is because of not only the limitation of the number of subjects but also the deficit of subject classification. The previous studies have not dealt with the individualities of the sprinters related to anthropometric factors. The difference in the length and the ratios of body segments depending on sprinters can change many biomechanical factors. For example, a difference of the length of arms of subjects can make difference in the alignment of upper body even though it is trivial. Future studies will have to take care of this issue and show whether there is a meaningful difference or not.